The Prairie Vole Model of Pair-Bonding and Its Sensitivity to Addictive Substances - Potretzke, Sheena; Ryabinin, Andrey E. (Frontiers in Psychology, 2019)
The prairie vole (Microtus ochrogaster) is an extensively studied model for understanding the neural mechanisms underlying social affiliations and pair-bonds. With clearly observed face and construct validity, this species offers translational insights into mechanisms involved in intimate relationships in humans. Moreover, the prairie vole model promises to advance our understanding- as well as allow for predictions- of the effects of extraneous factors (not normally encountered in nature) on such relationships. This mini-review describes some of the neurobiological mechanisms regulating social affiliation in prairie voles, followed by an overview of the effects of alcohol and other drugs of abuse on formation and maintenance of pair-bonds. Based on available literature, we demonstrate that the effects of such extraneous factors on formation and maintenance of pair-bonds are sex-dependent, as well as dependent on the specific nature of the addictive drug. In turn, the lack of similarities in effects of different addictive substances on pair-bond formation suggests that these substances engage different neurocircuits that may or may not overlap with neurocircuits involved in various social behaviors. This lack of consistency of effects across studied drugs of abuse indicates the need to further examine of effects of individual drugs on affiliative behaviors. We highlight the deficiencies in this field of research, particularly the sparsity of studies on effects of drugs of abuse on maintenance of established bonds. Future investigations in this field could help design strategies to help afflicted individuals.